EFFECT OF SOME HORMONAL TREATMENTS ON GROWTH AND CHEMICAL COMPOSITION OF RHAPHIOLEPIS UMBELLATA SHRUB - F. Saadawy; A. El- Fouly; A. Sayed (Scientific Journal of Flowers and Ornamental Plants, 2020)
A pot experiment was consummated on Rhaphiolepis umbellata seedlings grown under seran greenhouse at Al-Zohriya Garden, Hort. Res. Inst., ARC, Giza, Egypt during the two consecutive seasons 2017 and 2018, to study effects of five foliar spray treatments of a mixture containing three growth regulators (PGR), at the same concentration for each, on plant growth and chemical composition. The three-tested PGR were NAA, GA3 and BA, while the five concentrations for each were 0 (control treatment), 100, 200, 300 and 400 ppm. Obtained results indicated that, generally, all recorded vegetative and root growth traits; i.e., plant height, stem diameter, numbers of branches and number of leaves/plant, leaf area, root length and number of roots/plant increased significantly under the effect of all tested PGR treatments, compared to the control plants. The highest increases in this regard were recorded in plants sprayed with PGR at 200 ppm, while the least values were found in the untreated control plants, followed by plants sprayed with the highest PGR concentration of 400 ppm for the two seasons. The same trend was noticed in respect of leaf chemical constituents, as plants that recorded the highest vegetative and root growth (treated 200 ppm PGR) also contained the highest values of total chlorophyll and carotenoids (mg/g f.w.) as well as percentages oftotal carbohydrate, N, P and K in leaf tissues. Accordingly, it could be recommended to apply the mixture of these three growth regulators 200 ppm on seedlings of Rhaphiolepis umbellata, two times monthly during the growing season to get the best plant growth and quality.